Thinking about self-representation in the narrative-based Apartheid Archive Project - Gillian Eagle; Brett Bowman (Psychology in Society, 2010)
The article explores the role that a number of self-presentation related issues might play in the construction of the Apartheid Archive Project (AAP). It argues that both the web-based portal method of data collection, as well as the nature of the material being assembled - that being autobiographical accounts of recollections of racism under apartheid - suggest the likelihood of a particular kind of participation or subjectification on the part of many potential contributors. In constructing such narratives it has been observed that authors may seek to manage the manner in which they represent themselves and significant others in order both to meet the objectives of the AAP (as they interpret these) and simultaneously to manage self-esteem and the manner in which they are likely to become objects of scrutiny by others. Four central themes are discussed in order to elaborate aspects of self-representation that may be implicated in the AAP, these being: The Confessional Imperative; The Knowing Subject; The Restricted Repertoire of Identificatory Positions; and The Implication of Significant Others. Each of these is discussed in turn, together with some illustrative examples from the existing archive material. It is proposed that while these kinds of narrative influences may be inescapable in the assemblage of data of this kind, that it is important for those engaged in analysing and interpreting the contents of this archive to appreciate the ethical, methodological and epistemological tensions posed by this hypothesized aspect of the archival material.